A remarkably small new species of Filistata (Aranei: Filistatidae) from Portugal - Sergei L. Zonstein; Yuri M. Marusik; Arno Grabolle (KMK SCIENTIFIC PRESS LTD, MOSCOW STATE UNIV, 2022)
A new species, Filistata pygmaea sp.n., is described based on both sexes from Portugal. It is the smallest species among all Filistata known from the Mediterranean and Iran. Comparative figures of the vulva of all Filistata species ocurring west of Afghanistan are provided.